2012
DOI: 10.1016/j.jmu.2012.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Serial Ultrasonography for Early Detection and Follow-up of Heterotopic Ossification in Stroke

Abstract: KEY WORDSheterotopic ossification, stroke, ultrasonography Heterotopic ossification (HO) is a common complication in patients with neurologic deficits. Once developed, limited range of motion may occur and interfere with rehabilitation programs. Early diagnosis is crucial but difficult because radiographs may be negative, and similar clinical symptoms could appear in deep venous thrombosis, cellulitis, and osteomyelitis. A three-phase bone scan can detect the disease early, but it has high radiation and low sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…31 The case report indicated that serial ultrasonography (US) provided earlier and more specific diagnosis of a hip muscle HO lesion than did X-ray or MRI, the latter indicated necrotising fasciitis initially. 31 Ultrasonography depicted clear disease progression, with calcification visible on day 15 after onset of first symptoms. 31 Similarly, in the orthopaedic patients, US has high sensitivity and specificity for early HO diagnosis one week after total hip arthroplasty.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…31 The case report indicated that serial ultrasonography (US) provided earlier and more specific diagnosis of a hip muscle HO lesion than did X-ray or MRI, the latter indicated necrotising fasciitis initially. 31 Ultrasonography depicted clear disease progression, with calcification visible on day 15 after onset of first symptoms. 31 Similarly, in the orthopaedic patients, US has high sensitivity and specificity for early HO diagnosis one week after total hip arthroplasty.…”
Section: Resultsmentioning
confidence: 99%
“…Widely used diagnostic techniques have low sensitivity or specificity to incremental progression of mineralisation at early time points in HO development. 30 Yeh et al 31 reported that ectopic bone formation generally does not show on plain film until four to eight weeks after the initial symptoms. Without accurate and reliable early diagnosis, there is little chance of early intervention, and late detection fails to limit unabated progression of HO which often results in joint contractures, nerve entrapment and marked pain.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations